Whole house quick & easy projects. (Home Service Publications, Inc., 2021)
"A collection of 100+ beginner to intermediate-level Do-It-Yourself projects for homeowners, designed to be completed in a weekend or less, from Family Handyman magazine. With easy-to-follow, step-by-step instructions, the 100+ quick and easy projects in this book are just what you need to improve your backyard, your workshop, and all the rooms in your home. Plus, bonus Great Goofs are perfect for a work break--or advice on how NOT to get it done! Build it to last for years--in just a few days--with Whole House Quick & Easy Projects from Family Handyman."--Adapted from back cover.